Análisis de la producción de publicaciones científicas en inteligencia artificial aplicada a la formulación de Políticas Públicas - Sánchez-Céspedes, Juan Manuel; Rodríguez-Miranda, Juan Pablo; Salcedo-Parra, Octavio José (Revista Científica, 2020)
The objective of this article is to analyze the scientific publications made regarding the use of artificial intelligence tools in the decision-making process in the formulation of public policies. The methodology used was initially to create a search equation to locate the publications in this regard, which was tested and refined several times to improve the results found, this equation was applied in the SCOPUS database, with which 1.154 publications were obtained, to which bibliometric indicators were applied. The main results obtained were that this area has had great growth in the last decade, where the countries with the highest production are the United States, the People's Republic of China and the United Kingdom. By comparing scientific production with financing entities, it was possible to conclude the importance of government support for scientific development in a country.